Effect of internal flow on vortex-induced vibration dynamics of a flexible mining riser in external shear current. (November 2021) - Duan, Jinlong; Zhou, Jifu; You, Yunxiang; Wang, Xu
Abstract: Vortex-induced vibration (VIV) of flexible risers with both internal and external flows has received much attention recently. Hence, VIV dynamics of a fluid-conveying flexible riser subjected to external shear current is investigated. The effect of internal flow velocity and fluid density on VIV response is mainly examined and analyzed. A time domain model is introduced and elaborated. Then the finite element method is adopted to discretize the governing equations. Firstly, the model is validated based on the comparison between the numerical and experimental results. Then the influence of the internal flow velocity and fluid density on VIV dynamics is studied. The results show that multi-frequency response occurs when the flexible riser with various internal flow velocities and densities is subjected to external shear current. Under same shear current velocity, the IL mean deflection is enlarged with the increase of the internal flow velocity and fluid density. In addition, the internal flow velocity and fluid density have an evident effect on the vibrating frequency and the root mean square (RMS) displacement in both in-line (IL) and cross-flow (CF) directions. Moreover, mode and frequency transitions can be observed under different internal flow velocities and fluid densities. Highlights: Multi-mode and multi-frequency VIV response of the fluid-conveying riser occurs under external shear current. The IL mean deflection is amplified obviously with the increase of internal flow velocity and fluid density. The CF RMS displacement is magnified while the IL RMS displacement decreases due to the increase of internal flow velocity and fluid density. The IL and CF vibrating frequencies are decreased while the internal flow velocity and fluid density are increased.